The narratological approach in accompanying people towards the end of life: the experience of "Teatro DiLetto" - Malcotti, Ivano; Alfano, Linda; Ciliberti, Rosagemma (Medicina Historica, 2023)
Background: The care of patients in the terminal phase of their lives requires a broader approach that encompasses emotional, psychological, relational, and spiritual support for the person. Methodology: This paper describes the "TeatroDiLetto", a project aimed at exploring the possibility, for terminally ill patients, to express their experiences, stories, and emotions through various artistic forms, with the aim of promoting their emotional and psychological wellbeing and a better quality of care. The project involved three Italian associations dealing with healthcare support and a multidisciplinary group composed of: doctors, bioethicists, psychologists, therapists, and theatre actors. Training sessions were organised for the operators involved in the project, and individual interviews were conducted with all participants, before and after the artistic experience. Results and Discussion: Preliminary results suggest that the valorisation of patients’ narratives, life stories, memories, and wishes can have a significant impact on their well-being and on the quality of the operators’ professional performance, while fostering that sense of community and sharing among all those involved, which is the basis of any authentic care support process as well. Conclusions: Healthcare professionals should be prepared to interact with different humanities professionals, so that they might collaborate in the realisation of a personalised care project that is attentive to: the specific history of each subject, cultivating constant dialogue between knowledges, and drawing on a multiple and interactive panorama of competences.